ASAP! GIVING BRAINLIEST! Please read the question THEN answer CORRECTLY! NO guessing. I say no guessing because people usually guess on my questions.

ASAP GIVING BRAINLIEST Please read the question THEN answer CORRECTLY NO guessing I say no guessing because people usually guess on my questions class=

Respuesta :

Answer:

its b I belive

Step-by-step explanation:

Answer:

The answer is B.

Step-by-step explanation:

In order to find (f-g)(x), you have to subtract g(x) from f(x) :

[tex]f(x) = {3}^{x} + 10[/tex]

[tex]g(x) = 2x - 4[/tex]

[tex](f - g)(x) = {3}^{x} + 10 - 2x - ( - 4)[/tex]

[tex](f - g)(x) = {3}^{x} + 10 - 2x + 4[/tex]

[tex](f - g)(x) = {3}^{x} - 2x + 14[/tex]